Mengembangkan Kemampuan Interaksi Sosial Dengan Kegiatan Renang Pada Anak Usia Dini - Ella Putri Febria; Ima Nia Uliasari (Pusat Riset dan Inovasi Nasional, 2024)
Social behavior skills need to be taught since children are still small. In children's social development, the interactions they have with the people around them will have a strong influence on the formation of children's social-emotional behavior. This research aims to find out how the implementation of swimming activities develops the social interaction skills of early childhood at Mutiara Bunda Kindergarten. The method the author uses is descriptive qualitative. The research subjects were group B children aged 5-6 years with social interaction objects. Data collection tools use observation, interviews and documentation. The results of the research show that children's social interaction abilities develop because children are active in swimming, moving, able to adapt, express themselves, interact with friends, thus supporting children's social interaction abilities to be good.